Effects of integrated nutrient management on growth and yield of maize (Zea mays L.) - Gobhi sarson (Brassica napus L.) cropping system in sub-tropical region under foothills of north-west Himalayas (Bangladesh Journal of Botany, 2015)
A pronounced residual effect of organic and inorganic fertilizers, applied in maize crop was observed on yields of maize-gobhi sarson cropping system. The experiment was conducted with 10 treatments of N, P, K, FYM, crop residue and zinc sulphate nutrients. The highest growth, yield and yield components of maize crop were recorded with 100% recommended fertilizer dose-RFD + ZnSO4 20 kg/ha and the grain yield (2409 kg/ha) was about 101% higher over the control. In case of gobhi sarson, the highest seed yield (1081 kg/ha) was observed as a pronounced residual effect of 10 t/ha FYM in preceding maize crop; which was about 81% higher over the control. The treatments where 50% N was substituted by FYM and crop residue in maize crop had the best reflection in enhancing the seed yield of gobhi sarson to the tune of 74 and 70% over the control and 16 and 13% over farmers practice. The highest rain water use efficiency (RWUE) and heatuse efficiency (HUE) was recorded in treatment 100% RFD + ZnSO4 20 kg/ha in maize crop and 10 t/ha FYM in gobhi sarson. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21666 Bangladesh J. Bot. 43(2): 147-155, 2014 (September)